Pengaruh Tutorial Youtube Terhadap Kemampuan Mahasiswa dalam Menguasai Praktik Siklus Akuntansi di Universitas Negeri Makassar - Lulu Muarafah; Samsinar; Nuraisyiah (JIBEMA: Jurnal Ilmu Bisnis, Ekonomi, Manajemen, dan Akuntansi, 2026)
Video tutorials are instructional tools that have the capacity to improve the quality of teaching and learning, striving to arouse interest, stimulate thinking, and concretize knowledge that can otherwise only be discussed in abstract terms. This study aims to determine the effect of YouTube tutorials on students' ability to master accounting cycle practices at Makassar State University. Using a quantitative approach with data collection techniques conducted using questionnaires. Data analysis techniques were carried out using descriptive statistical analysis, instrument testing, and hypothesis testing with the help of the SPSS v. 24 for Windows program. The results of the analysis indicate that YouTube tutorials have a positive influence on students' ability to master accounting cycle practices. The regression coefficient indicates an increase in student ability each time there is an increase in YouTube tutorial use. The results of the partial test or t-test prove that YouTube tutorials have a significant effect on students' ability to master accounting cycle practices, so the hypothesis proposed in the study is declared accepted. Thus, YouTube tutorials are proven to make a real contribution to improving students' abilities in accounting cycle practices.